2021
DOI: 10.3389/fped.2021.671631
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and Eating Disorder and Risk of Subsequent Neurodevelopmental Disorders: A Population-Based Cohort Study

Abstract: Background: There are limited data concerning the long-term mental health of children with feeding and eating disorder (FED). We aimed to investigate whether children with FED are at greater risks of developing emotional/behavioral disorders with onset usually during childhood, attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), and intellectual disability (ID).Methods: We conducted a population-based cohort study, including all singleton births in Denmark from January 1, 1995, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…High rates of coexisting neurodevelopmental and medical conditions, including feeding disorders, in ASD has been highlighted since the 1980s (21,22), but particularly during the last decade (23)(24)(25)(26)(27)(28)(29). In 2010, Gillberg (30) launched the concept of Early Symptomatic Syndromes Eliciting Neurodevelopmental Clinical Examinations (ESSENCE), with a view to highlighting the overlap of symptoms and coexisting neurodevelopmental disorders in early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…High rates of coexisting neurodevelopmental and medical conditions, including feeding disorders, in ASD has been highlighted since the 1980s (21,22), but particularly during the last decade (23)(24)(25)(26)(27)(28)(29). In 2010, Gillberg (30) launched the concept of Early Symptomatic Syndromes Eliciting Neurodevelopmental Clinical Examinations (ESSENCE), with a view to highlighting the overlap of symptoms and coexisting neurodevelopmental disorders in early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…22 Another study found sex differences in NDC comorbidity with in children diagnosed with a feeding and eating disorder before age 3. 31 This study has several strengths. We investigated ARFID-related mental and somatic comorbidities in the largest reported sample of children and adolescents with the ARFID phenotype to date.…”
Section: Discussionmentioning
confidence: 98%
“…22 Another study found sex differences in NDC comorbidity with in children diagnosed with a feeding and eating disorder before age 3. 31…”
Section: Discussionmentioning
confidence: 99%
“…A specific cause of ED has not been established, but potential etiology includes genetic predisposition, cognitive and emotional vulnerability, social and environmental factors, such as pressure of the dominant cultural patterns and weight stigma ( 18 ). Moreover, in the group of children with ED, there are increased risks of emotional or behavioral disorders, attention-deficit/hyperactivity disorder and autism spectrum disorders ( 19 , 20 ).…”
Section: Epidemiologymentioning
confidence: 99%